Penerapan Model Pro Pintar Untuk Meningkatkan Hasil Belajar Dan Kemampuan Bekerjasama Siswa Dalam Pembelajaran Ips Di Kelas V Sdn Pandawan - Tita Rezky (CV. ITTC INDONESIA, 2024)
The research comes with the aim of improving learning outcomes and students cooperative skills in sicial studies learning of the PRO PINTAR (Problem Based Learning, Picture and Picture, Contextual Teaching and Learning, Talking Stick) model of grade fifth of SDN Pandawan. Applied research subjects. Data were obtained through observation efforts and learning outcomes tests that showed an increase: (1) teacher activity from 59,37% (adequate) in the first cycle of meeting 1 to 90,6% (very good) in the second cycle of meeting 2; (2) student activity from 53,8% (moderately active) to 88,1% (very active); (3) students cooperation ability from an average of 60 (incomplete) to 83,8 (complete). The application of the PRO PINTAR model has proven to be effective in improving learning outcomes and students ability to work togerther.